2005
DOI: 10.1136/thx.2004.035170
|View full text |Cite
|
Sign up to set email alerts
|

Biological dust exposure in the workplace is a risk factor for chronic obstructive pulmonary disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality. Although the main risk factor is smoking, 15-19% of COPD even in smokers has been attributed to occupational exposures. The aim of this study was to investigate the association between occupational exposure and risk of COPD. Methods: Participants were part of a cross sectional study of risk factors for COPD. A total of 1232 completed a detailed respiratory questionnaire, spirometric testsing and measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(118 citation statements)
references
References 34 publications
6
101
0
4
Order By: Relevance
“…All jobs for each individual were coded according to the Nordic Classification of Occupations system (15 We used the ALOHA-JEM to classify all the jobs that an individual had held with "no", "low" or "high" exposure to biological dust, mineral dust, and/or gas or fumes based on the ISCO-88 job codes (2,4,8). Thus, for each exposure type there were three exposure categories during follow up: (i) no job with exposure, (ii) at least one job with low exposure, but no high exposure, and (iii) at least one job with high exposure.…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…All jobs for each individual were coded according to the Nordic Classification of Occupations system (15 We used the ALOHA-JEM to classify all the jobs that an individual had held with "no", "low" or "high" exposure to biological dust, mineral dust, and/or gas or fumes based on the ISCO-88 job codes (2,4,8). Thus, for each exposure type there were three exposure categories during follow up: (i) no job with exposure, (ii) at least one job with low exposure, but no high exposure, and (iii) at least one job with high exposure.…”
Section: Questionnairesmentioning
confidence: 99%
“…Community studies and those on working populations have shown that airborne occupational exposure is related to asthma and respiratory symptoms (1)(2)(3)(4)(5). A paper on the Hordaland County Cohort Study showed that approximately 14% of incident adult asthma is attributable to occupational exposure in a general population (1).…”
mentioning
confidence: 99%
“…Recruitment and pulmonary-function testing were described in detail elsewhere (Matheson et al 2005). Briefly, 1,232 subjects (595 females, 637 males) were randomly recruited to be part of a two-stage crosssectional epidemiological study to investigate risk factors for asthma and COPD in adults aged between 45 and 69 years.…”
Section: Participantsmentioning
confidence: 99%
“…Nei pazienti con angina cronica stabile, la ranolazina riduce gli eventi ischemici ricorrenti 53 e migliora i livelli di emoglobina glicata nei pazienti diabetici data l'azione propria sulla secrezione insulinica. 54,55 Il miglioramento dei pazienti con angina cronica è dimostrato in vari trials che prendono in considerazione molteplici outcomes, come la performance alla prova da sforzo (durata, tempo d'esordio dell'angina, tempo di comparsa di alterazioni del tratto ST), [56][57][58] qualitĂ  di vita 59 e la frequenza degli episodi anginosi con necessitĂ  di assumere nitroglicerina. [60][61][62] Ranolazina è ben tollerata e i piĂš frequenti eventi avversi segnalati sono vertigini (11,8%), costipazione (10,9%) ed edemi periferici (8,3%).…”
Section: Ecg Da Sforzounclassified